Penyelenggaraan Jaringan Dokumentasi Informasi Hukum (JDIH) Online: Evaluasi Situs Web Pemerintah Daerah di Provinsi Jawa Timur - Pramono, Didik (Jurnal Ilmiah Administrasi Publik, 2015)
This paper explores the implementation of e-government through JDIH in East Java Province. Using descriptive quantitative analysis, this main findings show that the low capacity of IT related human resources and availability of updated information are the main challenge to improve e-government in the province. This study suggests the use integrated JDIH system or outsourcing of IT related human resources may able to improve the effectiveness of e-government.